Empowering the Tri Hita Karana Paradigm for the Community: As an Effort to Prevent and Combat Environmental Crime - Yusuf Saefudin; Bha'iq Roza Rakhmatullah; Fareed Mohd Hassan; Ma'ruf Ma'ruf; I Desak Ketut Dewi Satiawati Kurnianingsih (Ius et Ambientis, 2026)
Indexed by Scopus